(3GdeQLY aj GdGYdGe hGdGYdGe GdRQGYjs - (3eMeO YeQ(B, (3GdWfhHjs ((3GdGScfOQjI(B:s (3efTCI GdeYGQa HGdGScfOQjI(B,s, 1995)
(3GdEYdGe,GdEJUGd,GdUMGaI chSjdI EJUGd LeGgjQj,GdEPGYI GdeSehYI,GdJdjaRjhf chSjdI EJUGdjI LeGgjQjI,GdEYdGf,GdGYdGe hGdJfejIs
Keywords: (3GdGYdGes; (3GdRQGYIs